ALIGNING RECOUNT TEXT INSTRUCTION WITH THE EMANCIPATED CURRICULUM: INCLUSIVE EFL STRATEGIES FOR VISUALLY IMPAIRED LEARNERS - Rangkuti, Naufal; Setyarini, Sri; Rodliyah, Rojab Siti; Rakhmafithry, Dianty (Program Studi Magister Pendidikan Bahasa Inggris, Program Pascasarjana, Universitas Palangka Raya, 2025)
This study explores the alignment of English recount text modules with the Emancipated Curriculum and investigates the instructional strategies and assistive support employed in inclusive EFL classrooms for visually impaired learners. Using a qualitative descriptive method, data were collected through document analysis and classroom observation at a special needs school. The findings indicate that the learning modules generally adhere to the principles of flexibility, inclusivity, and student-centered learning, though some elements require refinement to better promote collaboration and higher-order thinking. Instructional strategies such as Discovery Learning and multisensory input were implemented, alongside assistive technologies like screen readers and Braille resources, which supported the development of receptive skills. However, challenges were found in resource availability, teacher training, and integration of assistive tools. Student responses revealed increased engagement and progress when inclusive and adaptive strategies were applied. These findings highlight the need for continued curriculum improvement, enhanced teacher preparation, and institutional support to ensure equitable EFL learning experiences for blind students.